ABAB Phthalocyanines: Scaffolds for Building Unprecedented Donor–π–Acceptor Chromophores. Issue 1 (27th December 2016) - Fazio, Ettore; Jaramillo‐García, Javier; Medel, María; Urbani, Maxence; Grätzel, Michael; Nazeerudin, Mohammad K.; de la Torre, Gema; Torres, Tomas
Abstract: Unique donor–π–acceptor phthalocyanines have been synthesized through the asymmetric functionalization of an ABAB phthalocyanine, crosswise functionalized with two iodine atoms through Pd‐catalyzed cross‐coupling reactions with adequate electron‐donor and electron‐acceptor moieties. These push–pull molecules have been optically and electrochemically characterized, and their ability to perform as chromophores for dye‐sensitized solar cells has been tested. Abstract : Push–pull chromophores : Unique donor–π–acceptor phthalocyanines are synthesized, and their ability to perform as chromophores for dye‐sensitized solar cells is tested.